BIOWAIVER STUDY OF IMMEDIATE RELEASE GLIMEPIRIDE TABLETS - ABDOUN, SIHAM; GABER, DALIA; ALWAHABI, RAGHAD; ALQUSSIR, NASHWA; ALMUTAIRI, NEHAL; ALSALAMAH, WAAD (International Journal of Applied Pharmaceutics, 2021)
Objective: Demonstrating therapeutic equivalency regarding the efficacy and safety among originator products and generics is a key step in permitting the marketing of generic products. The study aimed to evaluate the bioequivalence of five different generic brands of Glimepiride tablets under biowaiver conditions. Methods: The quality of the tablet products, including uniformity of weight, friability, and disintegration test, was assessed using the United State Pharmacopeia (USP) general monograph for the tablet dosage form. The content of glimepiride in the tablets was measured using UV spectrophotometer at the wavelength 229 nm. The release of Glimepiride from the tested and originator tablet products was evaluated using the dissolution profiles conducted in HCI buffer pH 1.2, and phosphate buffer pH 6.4 and 7.8 by USP dissolution apparatus II. The bioequivalence of test products was assessed using the similarity and difference factors. Results:The tested products complied to USP requirements for quality standards; all the products show rapid disintegration, D1 show higher time (Three minutes) while D3 show lower time (28 seconds). The content of test products was (104.68, 93.75, 97.21, 97.03, and 102.10) for D1, D2, D3, D4, and D5 , respectively, compare to 103.70 for OB. Dissolution profiles revealed that the highest similarity to the originator was showed in pH 6.4; f2 ranged (74.5-68.4) for all the tested products and low similarity in pH 7.8; f2 ranged (45.2-64.7). Conclusion: The study showed that the generic products has noticeable similarity with the originator brand and it can be interchangeable.